Testing the Response of the Annual Well-Being Index to Monthly Inflation in Iran: An Application of a Mixed-Data Sampling (MIDAS) Approach - Mani Motameni; Shahryar Zaroki; Arman Yousefi Barfurushi (برنامه‌ریزی و بودجه, 2023)
Curbing inflation is one of the requirements of a good economic policy. The steady rise of inflation can exacerbate poverty and income inequality, and even increase crime. Therefore, various studies have identified inflation as a determinant in reducing economic welfare. Considering that the Iranian economy has experienced high inflation in recent decades, it seems that the welfare of the Iranian population responds quickly to this variable, and reducing the frequency of data may reduce pattern explanation. This study attempts to measure the effect of monthly inflation on economic well-being for the period 1982-2020. Since the index of economic well-being cannot be determined at a frequency higher than annual, it is necessary to employ a mixed-data sampling (MIDAS) approach. Economic growth has been also included in the model as a control variable. The estimation results indicate that inflation has a negative (unfavorable) effect, and economic growth has a positive (favorable) effect on economic well-being. Moreover, the effect of inflation is significantly larger than economic growth. In other words, controlling inflation may have a greater effect on the economic well-being of society in the long term than economic growth.